Knowledge Levels Of Rest, Ice, Compression, Elevation Method With The Implementation Of Injury Handling In Sport Student Activity Units - Gita, Emmanuela Gst Ayu; Dian, Teuku Arief; Nawang, Galung (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2020)
Introduction: Sport is a regular movement perfomed by a person consciously to improve functional ability. Every sport has a risk of injury. Most amount of the injury get handled quickly, appropriately, and by a professional team will provide a good recovery and with no complications of disability or death. The best method to handle an injury is RICE method, Rest, Ice, Compression, and Elevation. Aim: This research purpose is to correlate between the knowledge levels with the implementation of injury handling in sport student activity units of Widya Mandala Catholic University Surabaya. Methods: This is an analytical method with cross sectional study and purposive sampling procedure. Total sample for this research is 95 students including the member of student activity unit of sport and have experienced sports injury. Member of this student activity unit consist of kyoukhusin, volleyball, badminton, basketball, taekwondo, and futsal. The knowledge levels and the implementation of injury handling measured by the knowledge levels and the application of injury handling questionnaire made by researcher. In this research used data analysis performed by Spearman correlation test. Result: The result of this research obtained with most less level of knowledge in sport student activity units do 2 application of injury handling is 26 person (27,4%). Conclusion: This research show that significant relation with p value is 0,000 that mean they have correlation between level of knowledge and the implementation of injury handling in sport student activity units of Widya Mandala Catholic University Surabaya and correlation coefficient value is 0,728 that show a strong positive correlation, therefore if they have less knowledge level so the implementation of injury handling will be less too.